An RDF Dataset Generator for the Social Network Benchmark with Real-World Coherence - Jovanovik, Milos; Spasić, Mirko; Prat-Pérez, Arnau (My University, 2016)
Synthetic datasets used in benchmarking need to mimic all characteristics of real-world datasets, in order to provide realistic benchmarking results. Synthetic RDF datasets usually show a ignificant discrepancy in the level of structuredness compared to real-world RDF datasets. This structural difference is important as it directly affects storage, indexing and querying. In this paper, we show that the synthetic RDF dataset used in the Social Network Benchmark is characterized with high-structuredness and therefore introduce modifications to the data generator so that it produces an RDF dataset with a real-worldstructuredness.
Keywords: Data Generation, Social Network Benchmark, Synthetic Data, Linked Data, Big Data, RDF, Benchmarks